Estudio de requerimientos para la Implementación de un módulo que permita imprimir los certificados de votación en línea en la página del Consejo Nacional Electoral - Calvache Santillan, Lilibeth Dayanara (2018)
In our country, the constitution is a fundamental law that helps all Ecuadorians to exercise rights and freedoms as citizens, as indicated in Article 6 "All Ecuadorians and Ecuadorians are citizens and enjoy the rights established in the Constitution." (ESilec , 2008), therefore all Ecuadorians and Ecuadorians have the right to Art. 217 "The Electoral Function will guarantee the exercise of political rights that are expressed through suffrage, as well as those referring to the political organization of citizenship." (eSilec, 2008), that is to say that all Ecuadorians have the right to vote, as a result a voting certificate is obtained as proof of suffrage, which is obligatory for all Ecuadorian citizens. The voting certificate in Ecuador is essential for any procedure in public or private entities in the country, a document that is only issued by the National Electoral Council and can be requested in any provincial delegation of the country. Currently this document is necessary in the procedures that you want to perform, prone to loss, deterioration, theft and other inconveniences that may arise. Due to these events that are presented, the respective procedure must be carried out to obtain them; it consists of approaching any provincial delegation to request the issuance of the voting certificate, at present there is no cost for the persons who have paid, for those who did not pay corresponds to pay the fine indicated by law. The disadvantage of citizens is the distance to travel, for people from distant cantons of the delegations of the province in which they are located, with a cost of mobilization and time to request a free document.